2010
DOI: 10.1016/j.tet.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazolidine 1-oxide systems for phosphine-free palladium-mediated catalysis

Abstract: NMP, NaOAc, TBAB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…Electronic effects have a great effect on the yield of coupling product. Although electron-withdrawing and electron-donating substituents on the aryl halide did not have a detrimental effect on the ability of the catalyst to promote this reaction to completion, aryl halides with electron-withdrawing groups gave higher yields than those with electron-donating substituents, which is similar to the M-H reaction reported previously (entries 10-12, 13 vs. [14][15][16][17][18]. This could also be confirmed by the observation that although it was difficult for bromobenzene to give a coupling product, a considerable improvement in yield in the case of 4-bromonitrobenzene was obtained due to the presence of strong electron-withdrawing substituent NO 2 on the phenyl ring (entry 20).…”
Section: Catalytic Activity Of Catalyst In the M-h Coupling Reactionsupporting
confidence: 81%
See 2 more Smart Citations
“…Electronic effects have a great effect on the yield of coupling product. Although electron-withdrawing and electron-donating substituents on the aryl halide did not have a detrimental effect on the ability of the catalyst to promote this reaction to completion, aryl halides with electron-withdrawing groups gave higher yields than those with electron-donating substituents, which is similar to the M-H reaction reported previously (entries 10-12, 13 vs. [14][15][16][17][18]. This could also be confirmed by the observation that although it was difficult for bromobenzene to give a coupling product, a considerable improvement in yield in the case of 4-bromonitrobenzene was obtained due to the presence of strong electron-withdrawing substituent NO 2 on the phenyl ring (entry 20).…”
Section: Catalytic Activity Of Catalyst In the M-h Coupling Reactionsupporting
confidence: 81%
“…Therefore, in order to obtain a higher yield, the reaction time should not be less than 24 h. In view of the fact that the yield of cinnamic acid increased slightly from 24 h to 48 h (entries 4,9), the reaction mixture usually refluxed for 24 h in subsequent experiments. To verify the effectiveness and generality of this procedure, the reactions of various aryl halides with acrylic acid were examined under the optimized reaction conditions ( Table 1, entries [10][11][12][13][14][15][16][17][18][19][20][21][22]. All of the present reactions were carried out in neat water without the need for phase transfer catalyst and protection from air, showing that the methodology has distinct advantages.…”
Section: Catalytic Activity Of Catalyst In the M-h Coupling Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…By varying the ligand structure and probing reaction conditions, catalyst loading as low as 0.00002 mol% were obtained and pre-prepared ligand-palladium conjugates were found to be easy to handle bench stable materials. 5 Roger et al showed that a wide range of aryl bromides could be employed in direct arylation of heteroaromatic species bearing unprotected alcohols. Scheme 2 shows the phosphine-free conditions employed in the direct arylation of thiophenecontaining substrates, providing ready access to a useful range of coupled products bearing formyl, ester, trifluoromethyl, fluoro, acetyl, nitro and nitrile functionality on the aromatic (Ar) fragment.…”
Section: Palladium Nobel Prizementioning
confidence: 99%
“…4 di-secondary amines including AM2, AM3, AM4, and AM6 were synthesized and fully characterized except the commercially available monomers. [36][37][38] (Scheme…”
Section: Introductionmentioning
confidence: 99%